2011
DOI: 10.1007/s00381-011-1578-7
|View full text |Cite
|
Sign up to set email alerts
|

The value of postoperative MR in tethered cord: a review of 140 cases

Abstract: Based on analysis of our series of 140 consecutive patients who all underwent POMR 6-18 months after TC release, we suggest that POMR as routine clinical practice is not justified for uncomplicated cases of TC release. In cases of high risk for retethering, or significant preoperative syrinx or dermoid, POMR is recommended to establish a baseline for future clinical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…postoperative CT scanning was not necessary as long as the patient was extubated within an hour after surgery and his or her neurological condition was closely monitored. Moreover, authors of different studies in oncological and skull base tumor surgery, 3,14,18,22 spinal surgery, 15 and pediatric cranial reconstruction 5 have concluded that routine scanning has little clinical impact if surgery was without complications and can usually be omitted in the absence of neurological or other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…postoperative CT scanning was not necessary as long as the patient was extubated within an hour after surgery and his or her neurological condition was closely monitored. Moreover, authors of different studies in oncological and skull base tumor surgery, 3,14,18,22 spinal surgery, 15 and pediatric cranial reconstruction 5 have concluded that routine scanning has little clinical impact if surgery was without complications and can usually be omitted in the absence of neurological or other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 140 cases of tethered cord consisting of 48 cases of lipomyelomeningocele demonstrated no advantage in obtaining routine postoperative follow-up MRI scans. 24 In this study, only a single reoperation was performed on lipomyelomeningocele, and that was prompted by clinical evaluation rather than imaging. Determining the need for a tethered cord release after primary repair of a lipomyelomeningocele therein remains largely a clinical decision based on neurological function rather than on radiological findings.…”
mentioning
confidence: 99%
“…TCS is usually associated with heterogeneous group of spinal dysraphism, such as diastematomyelia, lipoma, thickened filum, and myelomeningocele [12]. MRI is the modality of choice for evaluation of TCS [12] as it shows structural information required to assess, classify, and identify associated pathologies, and to plan treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the modality of choice for evaluation of TCS [12] as it shows structural information required to assess, classify, and identify associated pathologies, and to plan treatment. Our patients had combinations of all four pathologies.…”
Section: Discussionmentioning
confidence: 99%